Chronic Chagas disease with cardiodigestive involvement and the TcVI infective form of Trypanosoma cruzi. A case report - Vicco, Miguel Hernán (2012)
We report a patient with megacolon associated with TcVI infective lineage form of Trypanosoma cruzi. Although this megacolon was considered idiopathic, Chagas disease was suspected and diagnosed because of the concomitant cardiovascular involvement. Based on this case, we discuss the suitability of Chagas diagnosis in patients with tract motility involvement.